New Trends in Acute Management of Colonic Diverticular Bleeding: A Systematic Review. Issue 44 (November 2015) - Unknown
Abstract : Abstract: Colonic diverticular disease is the most common cause of lower gastrointestinal bleeding. In the past, this condition was usually managed with urgent colectomy. Recently, the development of endoscopy and interventional radiology has led to a change in the management of colonic diverticular bleeding. The aim of this systematic review is to define the best treatment for colonic diverticular bleeding. A systematic bibliographic research was performed on the online databases for studies (randomized controlled trials [RCTs], observational trials, case series, and case reports) published between 2005 and 2014, concerning patients admitted with a diagnosis of diverticular bleeding according to the PRISMA methodology. The outcomes of interest were: diagnosis of diverticulosis as source of bleeding; incidence of self-limiting diverticular bleeding; management of non self-limiting bleeding (endoscopy, angiography, surgery); and recurrent diverticular bleeding. Fourteen studies were retrieved for analysis. No RCTs were found. Eleven non-randomized clinical controlled trials (NRCCTs) were included in this systematic review. In all studies, the definitive diagnosis of diverticular bleeding was always made by urgent colonoscopy. The colonic diverticular bleeding stopped spontaneously in over 80% of the patients, but a re-bleeding was not rare. Recently, interventional endoscopy and angiography became the first-line approach, thus relegating emergency colectomy to patients presenting with hemodynamic instability or as a second-line treatment after failure or complications of hemostasis with less invasive treatments. Colonoscopy is effective to diagnose diverticular bleeding. Nowadays, interventional endoscopy and angiographic treatment have gained a leading role and colectomy should only be entertained in case of failure of the former.